2013
DOI: 10.1371/journal.pone.0084255
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Tuberculosis Case Finding among Malnourished Children in Nutritional Rehabilitation Centres of Karnataka, India: Missed Opportunities

Abstract: BackgroundSevere acute malnutrition (SAM) is the most serious form of malnutrition affecting children under-five and is associated with many infectious diseases including Tuberculosis (TB). In India, nutritional rehabilitation centres (NRCs) have been recently established for the management of SAM including TB. The National TB Programme (NTP) in India has introduced a revised algorithm for diagnosing paediatric TB. We aimed to examine whether NRCs adhered to these guidelines in diagnosing TB among SAM children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…8 Data on TB prevalence among acutely malnourished children vary widely: 2-24% of acutely malnourished children in high TB burden settings have been diagnosed with TB. [9][10][11][12][13] The wide range observed between studies can be partly attributed to the use of varying screening strategies and access to TB diagnostics, as well as varying clinical capacity for childhood TB diagnosis and treatment among hospitalized children. Even at referral hospitals, access to diagnostic tests may be limited, 14 highlighting the need for improved access to services across all levels of the health care system, including appropriate referral pathways.…”
Section: Tuberculosis and Malnutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Data on TB prevalence among acutely malnourished children vary widely: 2-24% of acutely malnourished children in high TB burden settings have been diagnosed with TB. [9][10][11][12][13] The wide range observed between studies can be partly attributed to the use of varying screening strategies and access to TB diagnostics, as well as varying clinical capacity for childhood TB diagnosis and treatment among hospitalized children. Even at referral hospitals, access to diagnostic tests may be limited, 14 highlighting the need for improved access to services across all levels of the health care system, including appropriate referral pathways.…”
Section: Tuberculosis and Malnutritionmentioning
confidence: 99%
“…This can be challenging, particularly in resource-limited settings. 12,13 In India, evaluating for TB among children treated for SAM at nutrition rehabilitation centers resulted in a TB diagnosis for 2-9% of children, and highlighted several challenges, such as lack of qualified health care providers, limited availability of CXR and TST, and difficulties with sputum collection. 12,13 These hurdles could be overcome by increasing the capacity of health care workers to diagnose TB clinically in the absence of diagnostic tests and/or the improvement of referral systems.…”
Section: Public Health Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…), virulence of the infecting organism and the immunology of the child [1, 79]. Cases of immunosuppression greatly increase this risk, such as age [1, 1012], malnutrition [13, 14], diabetes, tobacco and alcohol use, or human immunodeficiency virus (HIV)[15]. As stated before, TB remains a very real threat primarily in third-world countries and is in part due to these risk enhancers.…”
Section: The Global Tuberculosis Epidemic: a Focus On Pediatricsmentioning
confidence: 99%
“…Chisti et al 9 prospectively investigated causes of pneumonia in severely malnourished children aged ,5 years in a hospital in Bangladesh. Of 1482 children with severe malnutrition, 405 had respiratory symptoms and an abnormal chest radiograph; TB was confirmed microbiologically in 10 reviewed TB screening at nutritional rehabilitation centers in Karnataka, India, and found that a standardized TB diagnostic algorithm was followed for only 37% of the children. They also found operational challenges at the centers, including nonavailability of a pediatrician, nonfunctioning radiograph equipment, use of an inferior tuberculin solution, and poor training of the staff.…”
Section: Malnutrition and Pneumoniamentioning
confidence: 99%